1990
DOI: 10.1104/pp.93.4.1390
|View full text |Cite
|
Sign up to set email alerts
|

Slow Inactivation of Ribulosebisphosphate Carboxylase during Catalysis Is Caused by Accumulation of a Slow, Tight-Binding Inhibitor at the Catalytic Site

Abstract: The slow inactivation which accompanies catalysis by higherplant ribulose-P2 carboxylase-oxygenase (Rubisco) (2), such reactions could occur at the catalytic site as well as in solution.In this study, we show that a slow, tight-binding inhibitor is, indeed, responsible for fallover. The data are most consistent with the inhibitor being formed as a by-product during catalysis. MATERIALS AND METHODSRubisco2 becomes slowly inactivated during catalysis after exposure to ribulose-P2. This inactivation, or "fallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 24 publications
3
41
0
1
Order By: Relevance
“…Its apparently unimpaired tight binding of the reaction intermediate analog, carboxyarabinitol-P 2 , and its only slightly impaired capacity for enolization of the substrate indicate that perturbation of the active by the mutation must be quite subtle. Rubisco-Consistent with the view that fallover inhibition of Rubisco during catalysis is caused by accumulation of slow binding inhibitors at the active site (21,22), assay time-course data ( Fig. 1) fit well to Equation 1, which can be derived from the two-step, slow isomerization model (40) of slow inhibition (see "Experimental Procedures").…”
Section: Discussionsupporting
confidence: 76%
“…Its apparently unimpaired tight binding of the reaction intermediate analog, carboxyarabinitol-P 2 , and its only slightly impaired capacity for enolization of the substrate indicate that perturbation of the active by the mutation must be quite subtle. Rubisco-Consistent with the view that fallover inhibition of Rubisco during catalysis is caused by accumulation of slow binding inhibitors at the active site (21,22), assay time-course data ( Fig. 1) fit well to Equation 1, which can be derived from the two-step, slow isomerization model (40) of slow inhibition (see "Experimental Procedures").…”
Section: Discussionsupporting
confidence: 76%
“…4), which might be expected if it was caused by readily reversible binding of ribulose-P2 at a noncatalytic regulatory site as has been suggested by Yokota and Kitaoka (26). While this conclusion differs from that of Yokota and Kitaoka, our data are consistent with those ofSicher et al (24) for purified Rubisco, and this matter of reversibility is addressed further in the third paper of this series (7).…”
Section: Reversibilitysupporting
confidence: 61%
“…The enhanced inactivation occwring on exposure to subsaturating RuBP is thus a transitory phenomenon, which disappears quickly after RuBP exhaustion, whereupon the activity returns to approximately the leve1 that would have been observed following a similar period of exposure to saturating RuBP. On the other hand, Edmondson et al (1990~) showed that the inactivation occurring while RuBP is saturating persisted for hours after RuBP exhaustion, and even complete remova1 of small molecules from the enzyme solution by gel filtration induced only a limited recovery. For complete recovery, exposure to a high salt concentration during gel filtration or dialysis was required.…”
Section: Results At Saturating Comentioning
confidence: 99%
“…4 and 6). The production of inhibitory catalytic by-products is also likely to be increased by CO, limitation (Edmondson et al, 1990~). Exposure to subsaturating RuBP caused more extensive decarbamylation.…”
Section: Measurement Of Rubisco Carbamylationmentioning
confidence: 99%